SWARA SARONDER: SEBUAH KOMPOSISI KARAWITAN INTERPRETASI UNSUR TIGA DALAM INSTRUMEN GAMELAN JAWA - Suhardjono; Aji Santoso Nugroho (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2024)
Swara Saronder is a work of musical composition inspired by observations of Javanese gamelan and the triple phenomenon of the dominance of pencon-shaped instruments which form tiered strata sequentially from largest to smallest. Each of these instruments has different functions and tasks but forms a unified whole. The existence of three instrumental elements that dominate Javanese gamelan is a source and basis for the creation of musical compositions. Swara Saronder is a musical work that originates from the drumming techniques of the gender and saron groups. Personal experience as a gamelan composer (musician) was the inspiration for this musical composition. Because the technique of playing blade group instruments is interesting to study and develop as a reference for creating a musical composition work. The purpose of creation is to try to express musical anxiety towards Javanese gamelan in the form of interpretations of musical compositions that are not always bound by the rules of conventional musical form. The creation method/process is carried out through several stages, namely observing the source object, processing ideas and the process of pouring out the results.